Konsumsi Madu Untuk Peningkatan Hemoglobin Remaja Putri - Retno Widowati; Shinta Novelia; Yeremiah Rubin Camin; Deuis Sulastri (STKIP Andi Matappa, 2022)
This Community Service (CS) aims to increase Hb levels in adolescent girls with anemia by consuming honey regularly. CS was carried out in August 2021. The participants were members of Majelis Ta’lim Nurul Ikhlas Sukabumi. In the CS event, the participants were provided explanations about anemia and honey's benefits, and then Hb levels were checked. The girls with anemia were given honey for consumption. They consumed 10 ml of honey twice a day for 14 days. The results showed that the average Hb level before honey consumption was 10.460 g/dL and increased significantly to 12.730 g/dL. Anemia in adolescent girls could be prevented or overcome by consumption of honey regularly.